2012
DOI: 10.1007/s11548-012-0670-0
|View full text |Cite
|
Sign up to set email alerts
|

Segmentation and quantification of intra-ventricular/cerebral hemorrhage in CT scans by modified distance regularized level set evolution technique

Abstract: Purpose An automatic, accurate and fast segmentation of hemorrhage in brain Computed Tomography (CT) images is necessary for quantification and treatment planning when assessing a large number of data sets. Though manual segmentation is accurate, it is time consuming and tedious. Semi-automatic methods need user interactions and might introduce variability in results. Our study proposes a modified distance regularized level set evolution (MDRLSE) algorithm for hemorrhage segmentation. Methods Study data set … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 17 publications
(14 reference statements)
2
44
1
Order By: Relevance
“…CCCs for algorithms based on clustering, graph theory, and modified thresholding were 0.87, 0.91, and 0.97, respectively, and they are comparable to the CCCs calculated for our segmentation algorithm. 10,[29][30][31] This supports our approach to combine multiple segmentation strategies within a random forest model to tackle challenging segmentation tasks and is a promising distinction of our algorithm.…”
Section: Discussionmentioning
confidence: 52%
“…CCCs for algorithms based on clustering, graph theory, and modified thresholding were 0.87, 0.91, and 0.97, respectively, and they are comparable to the CCCs calculated for our segmentation algorithm. 10,[29][30][31] This supports our approach to combine multiple segmentation strategies within a random forest model to tackle challenging segmentation tasks and is a promising distinction of our algorithm.…”
Section: Discussionmentioning
confidence: 52%
“…Some researchers have extended the scope and performed the ICH segmentation to identify the region of ICH [7,11,15,17,[19][20][21][22][23][24][25][26]. Most researchers validated their algorithms using small datasets [7][8][9][10][11][12][13]17,[20][21][22][24][25][26], while a few used large datasets for testing and validating [6,[14][15][16]18,19,23]. We provide a comprehensive review of the published papers for the ICH detection and segmentation ( Figure 1) in this section.…”
Section: Related Workmentioning
confidence: 99%
“…It is essential to localize and find the ICH volume to decide on the appropriate medical and surgical intervention [27]. Several methods were proposed to automate the process of the ICH segmentation [7,11,15,17,[19][20][21][22][23][24][25][26]. Similar to the ICH detection, the ICH delineation approaches can be divided into traditional [7,11,[20][21][22]26] and deep learning methods [15,17,19,[23][24][25].…”
Section: Intracranial Hemorrhage Segmentationmentioning
confidence: 99%
“…Term R(φ) is employed to maintain a desired shape of the LSF, as it has been previously shown that the LSF usually becomes too flat or too steep near the zero level set, resulting in numerical errors which may eventually affect the stability of the evolution [13], [32], [50], [51]. Term Length(φ) is related to the energy along the length of the evolving contour C, i.e., for the case where φ =0; while term Area(φ) is related to the energy of the area inside of C, i.e., for the case where φ >=0.…”
Section: Weighted Level Set Evolutionmentioning
confidence: 99%